Diagnostic Testing and Antibiotic Use in Young Children With Community-Acquired Pneumonia in the United States, 2008–2015. (20th May 2019) - Florin, Todd A; Byczkowski, Terri; Gerber, Jeffrey S; Ruddy, Richard; Kuppermann, Nathan
Abstract: Diagnostic testing and antibiotics are not routinely recommended for young children with community-acquired pneumonia. In a national sample of >6 million outpatient 1- to 6-year-olds with community-acquired pneumonia between 2008 and 2015, a complete blood count was obtained for 8.6% (95% confidence interval [CI], 6.1%–11.1%), radiography was performed for 43% (95% CI, 36%–50%), and antibiotics were given for 73.9% (95% CI, 67.1%–80.7%). There were no changes in testing or antibiotic use over time.